PENGARUH BLENDEDDLEARNINGIBERBASISIMULTIIAPLIKASI UNTUK MENINGKATKAN HASILIBELAJARIMATEMATIKA PESERTA DIDIK SMPN 1 PADANG PANJANG - Zahara Ermanda Putri (Departemen Matematika, 2021)
Learning result are benchmarks used toodetermineetheeleveloof successsof studentsiin understanding concepts in learning. But in fact, judging by the final assessment scores offtheeeighthhgrade mathematicians offSMPN 1 Padang Panjang for the 2020/2021 school year, it is still low. One effort that can overcome these problems is to use a multi-application-based blended learning model in the mathematics learning process. Theepurposeeoffthissstudy was toddetermine and describe the mathematics learning outcomes ofsstudentsswho study withtthe multi-application-based Blended Learning model at SMPN 1 Padang Panjang. This type of research is a pre-experimental research with the design of the one shot case study. The subjects of this study were students in class IX E of SMPN 1 PadanggPanjang in the 2021/2022 academic year. The instrument used is a test of mathematics learninggresult in the formoof description questions, theedata obtained are thenaanalyzed with the one sample tttest. Basedoonnthe analysis of the researchddata, ittcannbe seen thataat theereal level α = 0.05, P-value =00.000 is obtained for the data on mathematics learning result, because the P-value < α, then reject H0. sooittcannbeeconcludedtthattthe blendeddlearninggmodel hasaan effectoon learning result, where theelearning outcomes oftthose who learn withhthe blendedllearningamodel are better than theeresultsoof previous studies. Keywords – blended learning, learning result, One shot case study design